THE EFFECT OF BAI, SIZE, OWNERSHIP, AND PROFITABILITY ON DISCLOSURE OF BIOLOGICAL ASSET - Atika Yunia Nuraeli Prasetia; Retno Martanti Endah Lestari; Abdul Kohar (Jurnal Magister Akuntansi Trisakti, 2023)
Data from the Ministry of Agriculture showed that during the Covid-19 pandemic, agricultural sector managed to increase the growth of GDP by 2.19% compared to the previous year (year-on-year). Then, data from the Central Bureau of Statistics shows in 2020, only the agricultural sector made a positive contribution of 1.75% to GDP compared to other business sectors. This needs to be the government's attention to develop the agricultural sector as a sector that is expected to be the main engine of development in order to realize the Sustainable Development Goals (SDGs). The intention of this research was to find out the effect from intensity of biological asset, firm size, managerial ownership and profitability on disclosure of biological assets in agricultural enterprises listed on the IDX from 2016 to 2020. This study falls under verification research category. All agricultural companies listed on IDX period 2016-2020 are the population in this research. Purposive sampling was used to choose the sample and 13 companies were chosen. Documentary studies were used to acquired data. In this study, data was collected utilizing a documentary study with analysis of multiple linear regression. In this study data processing using the help of IBM SPSS Ver.25.0. According to the findings of this study, firm size has a considerable favorable effect on the dsiclosure of biological assets. The intensity of biological assets, management ownership, and profitability no impact disclosure of biological assets. Thus, biologiccall aset intensity, firm size, managerial oownerhip, and profitability silmutaneously impact on biological aset disclosure.